How “wised up” are we in matters of climate change? - Agg Zoltán; Аґґ З. (ФОП Сабов А. М., 2019)
Abstract. In the so called sociological project where we examine the changes related to climate and environment as well as the transformation of values and attitudes and analyze the social contexts of these factors in today's Hungarian society. The environmental problems caused by climate change has already changed the way of thinking as of individuals and as of social groups, their relation to the environment, and the adverse consequences enhance the natural environment. It is our assumption that the importance of environmental considerations, their recognition and awareness, and the change of value system are determined by different groups of individual, individuals and communities. It can be influenced by the schooling, township and the age as well meanwhile differences can also be made on the basis of a worldview. Compared to domestic value sociological studies, the novelty of our research is precisely in the study of environmental values by social groups, group awareness, environmental changes and the transformation of value systems in an area where individuals, families and other communities are particularly sensitive to environmental sensitivity.
Наскільки заплутані ми в питаннях зміни клімату?
https://opac3.brff.monguz.hu/hu/record/-/record/bibBRF00007679
Keywords: climate change; environment